Excessive public indebtedness as a factor of ineffectiveness of the human right to good governance (2018)
The human being has always aspired to have better living conditions, so that, through the various forms of political organization that have been created for this purpose, it is considered that good governance is a human right consistent, among various tasks, in the efficient administration of public resources. In this sense, public administration is also considered a human right, since it constitutes one of the main ways to satisfy other human rights. Unfortunately, in the Mexican reality an excessive subnational indebtedness has been observed with greater frequency, which is generally produced by an inefficient public administration, which propitiates a budgetary decrease of the resources that will be destined to the satisfaction of other human rights, having as collateral effect that these rights have not been developed mechanisms of control nor measurement. The aim of this work is to highlight the progress made in Mexico City in the area of human rights effectiveness through a case of a reduction in the budget for metrobuses which, probably based on the methodology of the Office of the United Nations High Commissioner for Human Rights, will be used to develop indicators that will contribute to the development of this new stage of human rights.